Partitioning of naturally-occurring radionuclides (NORM) in Marcellus Shale produced fluids influenced by chemical matrix. Issue 4 (8th March 2016) - Nelson, Andrew W.; Johns, Adam J.; Eitrheim, Eric S.; Knight, Andrew W.; Basile, Madeline; Bettis III, E. Arthur; Schultz, Michael. K.; Forbes, Tori Z.
Abstract : Naturally-occurring radioactive materials (NORM) associated with unconventional drilling produced fluids from the Marcellus Shale have raised environmental concerns. Abstract : Naturally-occurring radioactive materials (NORM) associated with unconventional drilling produced fluids from the Marcellus Shale have raised environmental concerns. However, few investigations into the fundamental chemistry of NORM in Marcellus Shale produced fluids have been performed. Thus, we performed radiochemical experiments with Marcellus Shale produced fluids to understand the partitioning behavior of major radioelements of environmental health concern (uranium (U), thorium (Th), radium (Ra), lead (Pb), and polonium (Po)). We applied a novel radiotracer, 203 Pb, to understand the behavior of trace-levels of 210 Pb in these fluids. Ultrafiltration experiments indicated U, Th, and Po are particle reactive in Marcellus Shale produced fluids and Ra and Pb are soluble. Sediment partitioning experiments revealed that >99% of Ra does not adsorb to sediments in the presence of Marcellus Shale produced fluids. Further experiments indicated that although Ra adsorption is related to ionic strength, the concentrations of heavier alkaline earth metals (Ba, Sr) are stronger predictors of Ra solubility.